Analisis Gender dalam Perspektif Islam - Adliah, Adliah; Muchtar, M Ilham (PT. Intelek Cendikiawan Nusantara, 2025)
This article discusses the concept of gender in Islam based on normative, historical, and social perspectives. Islam affirms equality between men and women in aspects of piety, rights, obligations, as well as social and economic roles. Drawing on the Qur'an, hadith, and the opinions of classical and contemporary scholars, this article highlights how Islam offers a just system in gender relations. Although there are still challenges to patriarchal culture in practice, Islam teaches the principle of balance that encourages women's participation in education, economics, and law. This discussion is relevant in answering various modern challenges and offering solutions based on Islamic values that are fair and inclusive. A correct understanding of the concept of gender in Islam can be a solution to various problems such as discrimination against women, access to education, and the role of women in public and domestic spaces. Therefore, a more contextual interpretation is needed so that Islamic values in gender equality can be applied optimally in social life.